2010
DOI: 10.1111/j.1365-2419.2010.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale movements of the swordfish Xiphias gladius in the Southern California Bight

Abstract: This study reports on the fine-scale movements of swordfish (Xiphias gladius) outfitted with pop-off satellite archival transmitters (PSATs) in the Southern California Bight (SCB). PSATs were deployed on basking swordfish using traditional harpoon methods from 2004 to 2006. Transmitters were programmed for short-term deployment (2-90 days) and re-acquired using a signal direction finder. High-resolution (min )1 ) depth and temperature data from nine swordfish (approximately 45-120 kg) were collected (>193 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
89
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 29 publications
9
89
3
1
Order By: Relevance
“…Holts et al (1994) acoustically tracked one swordfish in the Southern California Bight for 24 h. Takahashi et al (2003) recovered an archival tag deployed on a swordfish off the coast of Japan and examined vertical movement patterns and inferred possible tracks for the 11 mo deployment. Sepulveda et al (2010) presented observations from 9 pop-up satellite archival tags (PSATs) that were deployed and recovered in the Southern California Bight, with deployments ranging be tween 1 and 89 d. Dewar et al (2011) compiled observations from 9 and 15 swordfish tagged in the central and eastern North Pacific, respectively (8 of which, dataset CA1, are also part of this study), with fish being at liberty for 5 to 287 d. Common results across all studies are diel vertical movement patterns with occasional basking events, more frequently observed nearshore. The influence of light, temperature, and oxygen on daytime and night-time depths were also investigated (Dewar et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Holts et al (1994) acoustically tracked one swordfish in the Southern California Bight for 24 h. Takahashi et al (2003) recovered an archival tag deployed on a swordfish off the coast of Japan and examined vertical movement patterns and inferred possible tracks for the 11 mo deployment. Sepulveda et al (2010) presented observations from 9 pop-up satellite archival tags (PSATs) that were deployed and recovered in the Southern California Bight, with deployments ranging be tween 1 and 89 d. Dewar et al (2011) compiled observations from 9 and 15 swordfish tagged in the central and eastern North Pacific, respectively (8 of which, dataset CA1, are also part of this study), with fish being at liberty for 5 to 287 d. Common results across all studies are diel vertical movement patterns with occasional basking events, more frequently observed nearshore. The influence of light, temperature, and oxygen on daytime and night-time depths were also investigated (Dewar et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The data retrieved has been critical to understanding the physical and physiological variables that relate fish behavior to its surrounding environment (Arnold and Dewar, 2001). Using electronic pop-up satellite tag (PSAT) technology, prior studies have shown swordfish moving against light so that during daylight hours they are found predominantly below the thermocline (300-1000 m), while night hours are spent above the thermocline in near-surface waters (Sepulveda et al, 2010;Lerner et al, 2013). These tagging studies also show that swordfish usually descend to depth one hour before sunrise and ascend after sunset.…”
Section: Introductionmentioning
confidence: 71%
“…Swordfish Xiphias gladius Linneaus, 1758 is a monogeneric species found circumglobally in tropical, subtropical, and temperate pelagic waters, where it supports numerous commercial fisheries (Sepulveda et al, 2010). The movement of swordfish is one of the most complex among pelagic fishes (Dewar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations